The lleuque forests of South Central Chile: a phytosociological study and syntaxonomical classification within South American temperate forests - Amigo, Javier; Rodríguez-Guitián, Manuel A.; Ramírez, Carlos (Lazaroa, 2011)
This paper is a phytosociological study of a forest community dominated by the lleuque (the Araucanian name for the podocarpaceae Prumnopitys andina). This is a mixed forest community with gymnosperm and broad-leaved trees growing in a temperate sub-Mediterranean climate, with a somewhat continental character within the very oceanic territory of Chile. The paper describes the new Nothofago obliquae-Prumnopitydetum andinae association, mostly located between the Bío-Bío and La Araucanía regions (parallels 36º to 40º south). We deal with the bioclimatic characteristics of the community, its biogeographical restrictions and its continuing presence in special topographical sites. The paper not only analyzes the floristic composition of the community in order to ascribe it syntaxonomically to the Wintero-Nothofagetea class, but also considers a number of floristic arrangements which support a reinterpretation of some syntaxa which are phytosociologically ranked as orders or classes.